Rent-seeking Practices in the Budget Policymaking Processes at Local Government: Case Studies in Indonesia - Salahudin Salahudin; Achmad Nurmandi; Kisman Karinda; Tinuk Dwi Cahyani (Journal of Government and Civil Society, 2022)
ABSTRACTThis paper tries to analyze and utilizes qualitative document content analysis as a means of understanding rent- seeking practices in fiscal policymaking processes. This study revealed that rent-seeking practices in fiscal policymaking in Malang City, Malang Regency, and Batu City, Indonesia, involved the practices of bribery, corruption, collusion, lobbying, negotiation, and transactional politics between regional leaders, bureaucrats, private actors, and political brokers. Rent-seeking practices trough informal policymaking have a strong positive correlation to corruption. It shows that corruption resulted from rent-seeking practices in fiscal policymaking in Malang City, Malang Regency, and Batu City. Transactional politics, negotiations, bribery, collusive relations, and lobbying were also involved in rent-seeking, ultimately resulting in corruption. Therefore, the new thesis of this research is that transactional relations, negotiation, collusion, bribery, and political lobbies between regional heads, bureaucracy, parliamentary politicians, brokers, and businessmen trigger corruption in the formulation of regional budget policies. This research confirms that the practices of rent-seeking take place through informal budget policy formulation, such a transactional relations, negotiation, collusion, bribery, and political lobbies that result in acts of corruption in budget policies. Keywords: Informal policymaking, fiscal politics, local government, corruption, budget policy ABSTRAKArtikel ini mencoba menganalisis dan menggunakan analisis konten dokumen kualitatif sebagai sarana untuk memahami praktik rent-seeking dalam proses pembuatan kebijakan anggaran. Studi ini mengungkapkan bahwa praktik rent-seeking dalam pembuatan kebijakan anggaran di Kota Malang, Kabupaten Malang, dan Kota Batu, Indonesia, melibatkan praktik penyuapan, korupsi, kolusi, lobi, negosiasi, dan politik transaksional antara pemimpin daerah, birokrat, aktor swasta, dan pialang politik. Praktik rent-seeking melalui pembuatan kebijakan informal memiliki korelasi positif yang kuat dengan korupsi. Hal ini menunjukkan bahwa korupsi dihasilkan dari praktik rent-seeking dalam pembuatan kebijakan anggaran di Kota Malang, Kabupaten Malang, dan Kota Batu. Politik transaksional, negosiasi, penyuapan, hubungan kolusi, dan lobi juga terlibat dalam rent-seeking, yang pada akhirnya mengakibatkan korupsi. Oleh karena itu, tesis baru dari penelitian ini adalah bahwa hubungan transaksional, negosiasi, kolusi, penyuapan, dan lobi-lobi politik antara kepala daerah, birokrasi, politisi parlemen, pialang, dan pengusaha memicu korupsi dalam perumusan kebijakan anggaran daerah. Penelitian ini menegaskan bahwa praktik rent-seeking terjadi melalui perumusan kebijakan anggaran informal yaitu hubungan transaksional, negosiasi, kolusi, penyuapan,dan lobi-lobi politik yang mengakibatkan tindakan korupsi dalam kebijakan anggaran.Kata kunci: Pembuatan kebijakan informal, politik anggaran, pemerintah daerah, korupsi, kebijakan anggaran